PENGARUH KINERJA KEUANGAN DAN INDIKATOR KESULITAN FINANSIL TERHADAP HARGA SAHAM BANK STUDI KASUS BANK BCA - Harsono Yoewono (Media Ekonomi, 2014)
The main problem of bank is maintaining 3 financial health indicators, namely on aspects of liquidity, profitability, and solvency. These three bank performance parameters are part of the CAMEL surveillance system, without a single M (management) that can only be taken into account by the Bank Supervisory Team from Bank Indonesia for each bank. The purpose of research to determine the level of financial and financial performance of banks and the level of difficulty of banks that have gone public in Indonesia to the stock price of banks. This study was conducted to determine the impact of four groups of financial indicators on stocks, especially size of rentability, liquidity, solvency, and financial size. The various combinations of these 4 groups of indicators yield 45 independent variables that are estimated to affect the price and the number of 13 variables excluded, automatically by SPSS, in the estimation process. Of the 32 free variable, only 9 independent variables significantly affect stock price variables. The 9 independent variables are working capital (p5), cash ratio (q1), bank strength level (r3), sales (r9), operational (r8), financial burden indicator (s5), credit in rupiah (x2), investment non-credit (x4) and ROI (x5b).